2009
DOI: 10.1007/s11427-009-0096-2
|View full text |Cite
|
Sign up to set email alerts
|

Human parthenogenetic embryonic stem cells: one potential resource for cell therapy

Abstract: Pluripotent stem cells derived from somatic cells through such processes as nuclear transfer or induced pluripotent stem (iPS) cells present an important model for biomedical research and provide potential resources for cell replacement therapies. However, the overall efficiency of the conversional nuclear transfer is very low and the safety issue remains a major concern for iPS cells. Embryonic stem cells (ESCs) generated from parthenogenetic embryos are one attractive alternative as a source of histocompatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…While using normal human embryos to derive ES cells is ethically disputable, using parthenogenetic embryos (called ''parthenotes''), which are incapable of developing into full organisms, is less disputable (Sturm et al, 1994;Kono et al, 1996;Mognetti and Sakkas, 1996). In fact, many recent studies have demonstrated that parthenogenesis is an efficient way to generate histocompatible human embryonic stem (ES) cells for transplantation-based stem cell therapies (Revazova et al, 2008;Hao et al, 2009;Lu et al, 2010). Histocompatible parthenote ES cells represent an important milestone in stem cell therapies, as they allow partial MHC matching to a substantial population of unrelated transplant recipients (Cheng, 2008;Revazova et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…While using normal human embryos to derive ES cells is ethically disputable, using parthenogenetic embryos (called ''parthenotes''), which are incapable of developing into full organisms, is less disputable (Sturm et al, 1994;Kono et al, 1996;Mognetti and Sakkas, 1996). In fact, many recent studies have demonstrated that parthenogenesis is an efficient way to generate histocompatible human embryonic stem (ES) cells for transplantation-based stem cell therapies (Revazova et al, 2008;Hao et al, 2009;Lu et al, 2010). Histocompatible parthenote ES cells represent an important milestone in stem cell therapies, as they allow partial MHC matching to a substantial population of unrelated transplant recipients (Cheng, 2008;Revazova et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The basic data among stem cell-based therapy in diabetic patient population are presented in Table 2. However, the overall efficiency of the conversional nuclear transfer is very low and the safety issue remains a major concern for induced PSCs implementation in various DM patient populations [59] . Overall, the results of the recent studies are controversial due to lack uniformity of design and protocols related techniques of the cell isolation and delivery methods [33] .…”
Section: Expectancies Of Stem Cell-based Therapy In Diabetic Patient mentioning
confidence: 99%
“…However, not only is there the possible difficulty of considering the biopsy itself totipotent (and therefore worthy of protection), but it also seems naive to assume that embryo viability would not be affected by the procedure, and a more ethical possibility might be to use this technique only on embryos that were already undergoing pre-implantation genetic diagnosis. Yet another strategy is parthenogenesis 32 where an oocyte is stimulated to develop as if it had been fertilized. Parthenogenetic embryos have grown to the blastocyst stage (when pluripotent stem cells are harvested), although these cells show differences when compared with other embryonic stem cells.…”
Section: Pluripotent Stem Cell Research: Embryo Destruction Versus Nomentioning
confidence: 99%